(untitled) (International Journal of Bamboo and Rattan, 2023)
The Sustainable Development Goal, number 7, aims at ensuring access to clean and affordable energy, which is key to the development of agriculture, business, communications, education, healthcare, and transportation. Therefore, Energy is central to the achievement of both the 2030 Agenda for Sustainable Development and the Paris Agreement on climate change. Our desire for advancing SDG 7 would mean proactive actions that can catalyze the achievements of meeting the Paris Agreement on climate change and reach the other SDGs including poverty eradication, gender equality, mitigation of and adaptation to climate change, food security, health, education, sustainable cities and communities, clean water and sanitation, jobs, innovation, and transport. Energy transition refers to the global energy sector’s shift from fossil-based systems of energy production and consumption — including oil, natural gas, and coal — to renewable energy sources like wind and solar, as well as lithium-ion batteries.